Controversies on intuition, economic decision making - Guerra Heredia, Luis Arturo (2018)
In the history of human thought, the study of intuition, Platon, Descartes, Kant, etc., has been given importance. They have taken a position on this, however, the concept of intuition is still not clear and an idealistic or metaphysical concept is still being given. Picking up neuroscience theses, we discover that intuition is not irrational, it is a tacit knowledge that has to do with practical experience, and even cells called fusiform, which could be part of it, have been discovered. On the other hand, decision making has been studied over many years, and in neo-classical theory, rationality of the consumer is considered as one of the postulates, a thesis that was questioned by Kannemann and reinforced by Ariely, giving more force to the emotions in making decisions. Collecting the thesis of neuroscience, we discover that decision-making takes place around motivations, interests and attitudes, which in turn respond to the person’s tradition, culture and economy. Thus it is discovered that there is no controversy between rationality and intuition, and that decision-making considers intuition in such a way that every decision is a product of some measure of intuition, although it does not always influence it.